Antidepressant-Like Effect of Venlafaxine Is Abolished in μ-Opioid Receptor–Knockout Mice - Soichiro Ide (Journal of Pharmacological Sciences, 2010)
Although the opioid system is known to modulate depression-like behaviors, its role in the effects of antidepressants is not yet clear. We investigated the role of μ-opioid receptors (MOPs) in the effects of venlafaxine, a serotonin and norepinephrine reuptake inhibitor, in the forced swim test using MOP–knockout (KO) mice. Venlafaxine reduced immobility time in wild-type mice (C57BL/6J), but not in MOP-KO mice, although no significant effects were observed on locomotor activity. These results suggest that MOPs play an important role in the antidepressant-like effects of venlafaxine. Keywords:: μ-opioid receptor, knockout mouse, antidepressant